KEMAMPUAN KONEKSI MATEMATIS DALAM PENYELESAIAN MASALAH SPLDV PADA SISWA SMP - Taufik, Arohman; Wibowo, Teguh; Zainudin, Bisri (Jurnal Inovasi Pendidikan Matematika (JIPM), 2019)
This research aims to describe the mathematical connection in problem solving. Metode of qualitative research. The subject of this study were two ninth graders of junior high school in with a purposive technique. The research instrument was a mathematical connection test problem. The data analysis technique uses three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that students complate aspects of mathematical connections, namely: Aspects of mathematical connections in mathematical problems such as: Students understand the relationship between existing mathematical topics by writing down the equation model as ideas of the problems. Students are able to find the relationship between existing procedures and other procedures in representation with the equivalent concept shown by writing the two-variable linear system material equation. Students apply the relationship between mathematics, and between mathematical material with mathematical material by finding the value of equations. Students are able to use mathematical connections with mathematics or other fields of science using mathematics with economics to determine the number of purchases with capital, and aspects of mathematical connections with everyday life, namely; Students use procedures and concepts from one another according to the question data. The ability of students to use mathematics in everyday life in the context of buying and selling using capital, amount, profit. So, as a whole the mathematical connection ability of junior high school students complate the indicators and into the high connection category. Keywords: mathematical connection, two-variable linear system material, connection aspects.